Nutrient Fluxes from the Kamchatka and Penzhina Rivers and Their Impact on Coastal Ecosystems on Both Sides of the Kamchatka Peninsula - Pavel Semkin; Galina Pavlova; Vyacheslav Lobanov; Kirill Baigubekov; Yuri Barabanshchikov; Sergey Gorin; Maria Shvetsova; Elena Shkirnikova; Olga Ulanova; Anna Ryumina; Ekaterina Lepskaya; Yuliya Fedorets; et al. (Journal of Marine Science and Engineering)
Catchment areas on volcanic territories in different regions are of great interest since they are enriched with nutrients that contribute significantly to coastal ecosystems. The Kamchatka Peninsula is one of the most active volcanic regions of the world; however, to date, the chemistry of its river waters and the state of its coastal ecosystems remain understudied in connection with volcanism. The two rivers under study are the largest in this region. The Kamchatka River, unlike the Penzhina River, drains volcanic territories, including the areas of the most active volcanoes of the Klyuchevskaya group of volcanoes and the Shiveluch Volcano. The mouth of the Kamchatka River has been shown to have DIP and DIN concentrations of 2.79–3.87 and 10.0–23.8 µM, respectively, during different seasons, which are comparable to rivers in urbanized areas with sewerage and agricultural sources of nutrients. It has been established that volcanoes form high concentrations of nutrients in the catchment area of the Kamchatka River. The Penzhina River has had very low DIP and DIN concentrations of 0.2–0.8 and 0.17–0.35 µM, respectively, near the mouth during different seasons, but high concentrations of DOC, at 5.9 mg/L in spring, which may be due to seasonal thawing of permafrost. During the period of increasing river discharge, seasonal phytoplankton blooms occur in spring and summer in bays of the same name, as shown using satellite data. The biomass of zooplankton in Penzhina Bay is at a level of 100 mg/L, while in Kamchatka Gulf, it exceeds 2000 mg/L. Thus, the biomass of zooplankton in the receiving basin, which is influenced by the runoff of the Kamchatka River with a volcanic catchment area in eastern Kamchatka, is 20 times higher than in the basin, which has a small nutrient flux with the river runoff in northwestern Kamchatka. This study demonstrates the connection between nutrient fluxes from a catchment area and the formation of seasonal phytoplankton blooms and high zooplankton biomass in the coastal area. We also study seasonal, year-to-year, and climatic variability of water discharges and hydrometeorological conditions to understand how nutrient fluxes can change in the foreseeable future and influence coastal ecosystems.